Tanzania Poverty, Growth, and Public Transfers : Options for a National Productive Safety Net Program - Smith, W. James (World Bank, Washington, DC, 2014)
This report reviews the role that safety nets have played in Tanzania and explores options on how they can contribute in accelerating poverty reduction in Tanzania, focusing on mechanisms for giving transfers to the poor. The report shows that given the large numbers of poor in Tanzania and the country s limited resources, it is essential that safety net interventions be well-targeted and efficiently organized. Significant amounts of money are already being spent on transfer programs in Tanzania, but their impact has been limited. The report recommends that for Tanzania, a single intervention will not be enough to effectively tackle extreme poverty but a combination of different type of cash transfer options is more likely to make a difference in the strategy to reduce extreme poverty and food insecurity.